Inhibition of triggering receptor expressed on myeloid cells‐1 impairs thrombin generation. (27th November 2019) - Di Pillo, Elisa; Carrasco, Kevin; Brustolin, Benjamin; Boufenzer, Amir; Jolly, Lucie; Derive, Marc; Lacolley, Patrick; Regnault, Véronique; Gibot, Sébastien
Abstract: Background: New evidence has shown the link between inflammation and thrombosis. Triggering receptor expressed on myeloid cells‐1 (TREM‐1) is an immunoreceptor expressed mostly on neutrophils and monocytes/macrophages. TREM‐1 acts as an amplifier of the inflammatory response, and its pharmacological inhibition displays protective effects in various models of inflammatory disorders, in particular by dampening coagulation abnormalities and thrombocytopenia observed during acute inflammation. Objectives: We aimed to decipher the role of TREM‐1 in fostering thrombin generation. Methods: We measured thrombin generation (TG) by the use of calibrated automated thrombography with whole blood, and isolated primary human neutrophils and monocytes upon stimulation with lipopolysaccharide (LPS). Tissue factor (TF) expression was measured by flow cytometry and its activity by ELISA. Phosphatidylserine (PtdSer) exposure was determined by flow cytometry. A dodecapeptide (LR12) was used as a specific inhibitor of TREM‐1. Results: LPS increased TG, TF expression, and activity, as well as the exposure of PtdSer on the surface of monocytes. LR12 dampened TF activity through the decrease of PtdSer exposure, leading to a reduction of thrombin generation. Conclusions: TREM‐1 inhibition decreases thrombin generation and could be an interesting target for the development of new inhibitors of leukocyte‐associated thrombotic activity.